Decursin inhibits the growth of HepG2 hepatocellular carcinoma cells via Hippo/YAP signaling pathway. (24th September 2018) - Li, Jianchun; Wang, Honglian; Wang, Lu; Tan, Ruizhi; Zhu, Menglian; Zhong, Xia; Zhang, Yuwei; Chen, Bo; Wang, Li
Abstract : Targeted therapy has a pivotal role for the treatment of liver cancer. The aim of this current study was to examine the effects of decursin on the growth of HepG2 cells and the underlying mechanisms. Our present study showed that treatment of HepG2 cells with decursin significantly inhibited the growth of HepG2 cells by suppressing cell proliferation, cell cycle arresting, and promoting apoptosis in a dose‐ and time‐dependent manner. Most significantly, administration of decursin dramatically impeded in vivo tumor growth in nude mice. Mechanically, it is noteworthy that decursin treatment provoked degradation of YAP by upregulating the expression of phosphorylated LATS1 and βTRCP. Moreover, apoptosis caused by decursin could be reversed by a selective MST1/2 inhibitor, XMU‐MP‐1, suggesting that decursin may function through Hippo/YAP signaling. This study has identified that decursin is a potential agent for HCC therapy, and further research should be undertaken to facilitate its therapeutic application.